PENGARUH KUALITAS PRODUK, CITRA MEREK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MELALUI SHOPEE - Romadon, Ahmad Sahri; Pramusinto, Meirisa Andini; Kamelia, Salwa Nur (Fakultas Ekonomi, Universitas Semarang, 2023)
This study was to determine the effect of product quality, brand image and price on purchasing decisions through Shopee for Semarang city students. The population of this study are customers or shopee users who are students in the city of Semarang. The number of samples taken in this study is not known with certainty. The research method used is the quantitative method, the data analysis technique uses multiple linear regression analysis and validity test, reliability test whose data is processed with SPSS. Many respondents in this study were 96 respondents. With the results of product quality has a significant effect on purchasing decisions. Brand image has a significant effect on purchasing decisions. And price has a significant effect on purchasing decisions. It can be explained that: from the t test it can be explained that product quality, brand image and price partially have a significant effect on purchasing decisions through Shopee for Semarang city students where each independent variable (product quality, brand image and price) has a t sig value <0 ,05. From the F test it can be explained that product quality, brand image and price simultaneously have a significant effect on purchasing decisions through Shopee for Semarang city students where the F value is sig. of 0.042 <0.05. From the analysis of the coefficient of determination it can be explained that product quality, brand image and price influence purchasing decisions through Shopee for Semarang city students by 30.4%, while the remaining 69.6% are influenced by other variables outside this research model.